Про монографію А. Волоха «Мисливські звірі степової України» - Наконечний, І. (Theriologia Ukrainica, 2019)
Стисла характеристика змісту і значимості монографії проф. Анатолія Волоха про мисливських звірів півдня України. Книгу видано у двох частинах: частину 1 видано 2014 року в обсязі 412 стор., частину 2 — 2015 року в обсязі 201 стор. Книги видано з рецензіями проф. І. Ємельянова та проф. Є. Писанця. У першому томі (глави 1–6) розглянуто умови проживання, фауну, динаміку ареалів, біотопи і сховища, розмноження та віко-статеву структуру, смертність і хвороби. У томі 2, що включає глави подовженої нумерації (глави 7–11), представлено морфологічну характеристику видів, динаміку їхньої чисельності, соціальну організацію популяцій копитних, управління ресурсами та охорону ссавців. Brief description of the content and significance of the monograph by Prof. Anatoliy Volokh about game mammals of the south of Ukraine is presented. The book consists of two parts: part 1 was published in 2014 on 412 pages, part 2 in 2015 on 201 pages. The books were reviewed by Prof. I. Emelyanov and Prof. E. Pysanets. In the first volume (chapters 1–6), detailed analysis of habitats, fauna, dynamics of ranges, biotopes and shelters, reproduction and age-sex structure, mortality and diseases are presented. In volume 2 (chapter 7–11) the following data are presented: morphological characteristics of mammals, abundance dynamics of game mammals, social organization of ungulate populations, management of resources and conservation of mammals.